2018
DOI: 10.2147/ijn.s162262
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous diopside modulates biocompatibility, degradability and osteogenesis of bioactive scaffolds of gliadin-based composites for new bone formation

Abstract: IntroductionIt is predicted that with increased life expectancy in the whole world, there will be a greater demand for synthetic biomedical materials to repair or regenerate lost, injured or diseased tissues. Natural polymers, as biomedical materials, have been widely applied in the field of regenerative medicine.Materials and methodsBy incorporation of nanoporous diopside bioglass (nDPB) into glia-din (GL) matrix, macro–nanoporous scaffolds of nDPB/GL composites (DGC) were fabricated by method of solution com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…12 , 27 The porosity of biomaterials plays a vital role in bone formation, and the appropriate porosity would enhance the progression of osteogenesis. 28 , 29 In the future, we will further investigate the relationship between the porosity and mechanical strength of the PLGA/ATT composite nanofibers used for bone regeneration, which will enable the fabrication of scaffolds with morphological and mechanical properties needed for bone repair with a particular design.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 27 The porosity of biomaterials plays a vital role in bone formation, and the appropriate porosity would enhance the progression of osteogenesis. 28 , 29 In the future, we will further investigate the relationship between the porosity and mechanical strength of the PLGA/ATT composite nanofibers used for bone regeneration, which will enable the fabrication of scaffolds with morphological and mechanical properties needed for bone repair with a particular design.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis demonstrated that the expression of type I collagen increased with increasing glass content, indicating excellent pro-osteogenic properties. Scaffold degradation varied with glass content, and was found to be consistently more advanced for higher glass content [36].…”
Section: Collagen Gelatin Cellulose Chitosan and Other Biopolymersmentioning
confidence: 92%
“…The anodized nanoporous surface offers good mechanical retention and the pores are controlled in size to allow efficient transport of factors and proteins useful for the osseointegration process. This type of surface therefore allows the proliferation of osteoblastic cells, but also of connective tissue cells and epithelial cells, having instead a negative activity in the formation of a biofilm [7,8].…”
Section: Bioactive Nano Technology and Biomedical Applicationmentioning
confidence: 99%
“…The possibility to realize a biomaterial working on its nanostructure gives both the clinicians and researchers a unique set of opportunities. The usual way to create tissue engineered implants relies on providing a desired element homogeneously throughout a biomaterial, which is related to top-down tissue engineering [1,2,3,4,5,6,7,8].…”
Section: Bioactive Nano Technology and Biomedical Applicationmentioning
confidence: 99%